Self-Generated Versus Other-Generated Statements and Impressions in Computer-Mediated Communication: A Test of Warranting Theory Using Facebook. - Walther, Joseph B.; Van Der Heide, Brandon; Hamel, Lauren M.; Shulman, Hillary C. (Communication Research, 2009)
The warranting principle pertains to impression formation in Internet communication. It posits that perceivers' judgments about a target rely more heavily on information which the targets themselves cannot manipulate than on self-descriptions. Two experiments employed mock-up profiles resembling the Internet site, Facebook, to display selfgenerated clues and to display other-generated clues about a Facebook user. The first experiment (N = 115) tested perceptions of extraversion. Although warranting was supported, rival explanations (negativity and additivity) also pertained. The second experiment (N = 125) tested perceptions of physical attractiveness. Friends' comments overrode self-comments, supporting warranting theory exclusively. Implications concern boundary-setting research for warranting, and potential effects of social comments on a variety of new information forms.